Relationship Between Self Efficacy and Emotional Intelligence to Burnout In Nurses At Pakuhaji Hospital - Miftahul Aini, Intan; Diel, M. Martono; Pratiwi, Ayu (Jurnal Riset Media Keperawatan, 2025)
Background: Burnout is physical, mental and emotional exhaustion that occurs due to stress suffered over a long period of time, which demands high emotional involvement. High self efficacy helps individuals to complete tasks and reduce burnout related to their ability to control themselves and emotional intelligence helps nurses to understand emotions that occur both in themselves and others so that they become more engaged and the tendency for burnout experienced will be low. Objective: This study aims to determine the relationship between self efficacy and emotional intelligence to burnout in nurses. Method: the method in this study uses a cross sectional approach, the sampling technique uses a total sampling technique with a total of 97 respondents at Pakuhaji Hospital. Data were collected through questionnaires. Data analysis was carried out using univariate and bivariate analysis with the Chi-Square test. The results of the Chi-Square statistical analysis showed that there was a relationship between self-efficacy (p = 0.038) and emotional intelligence (p = 0.038) on burnout in nurses at Pakuhaji Regional Hospital. The overall results showed that there was a significant relationship between self-efficacy and emotional intelligence on burnout in nurses at Pakuhaji Regional Hospital